The Lewis acidity of boron trihalides revisited - Franca, Carlos Alberto (2009)
The relative Lewis acidity of boron trihalides is analyzed within the framework of modern density functional theory using larger basis sets that include both polarization and diffuse functions. Concepts such as the strength of the B-X pπ bonding and vertical electron affinities, as well as geometry and energetic features of complexes formed with ammonia are revisited. Notions often used in Basic Inorganic Chemistry courses to explain the Lewis acidity of boron trihalides are critically reviewed.